2016
DOI: 10.1016/j.redox.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate enhances key enzymatic activities of hepatic thioredoxin and glutathione systems in selenium-optimal mice but activates hepatic Nrf2 responses in selenium-deficient mice

Abstract: Selenium participates in the antioxidant defense mainly through a class of selenoproteins, including thioredoxin reductase. Epigallocatechin-3-gallate (EGCG) is the most abundant and biologically active catechin in green tea. Depending upon the dose and biological systems, EGCG may function either as an antioxidant or as an inducer of antioxidant defense via its pro-oxidant action or other unidentified mechanisms. By manipulating the selenium status, the present study investigated the interactions of EGCG with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 72 publications
1
36
0
1
Order By: Relevance
“…Thus, the effects of Se can also result from its effect on the expression of Nrf2, a master transcription factor that regulates the expression of antioxidant proteins. A previous study showed that the influence of epigallocatechin-3-gallate on the intracellular Nrf2 levels was removed in Se-optimal mice [37]. Upon oxidative stress, the ubiquitination of Nrf2 stops.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effects of Se can also result from its effect on the expression of Nrf2, a master transcription factor that regulates the expression of antioxidant proteins. A previous study showed that the influence of epigallocatechin-3-gallate on the intracellular Nrf2 levels was removed in Se-optimal mice [37]. Upon oxidative stress, the ubiquitination of Nrf2 stops.…”
Section: Discussionmentioning
confidence: 99%
“…In at least 13 animal models for human carcinogenesis of the lung, oral cavity, esophagus, stomach, small intestine, colorectal, colon, skin, liver, pancreas, bladder, prostate, or mammary glands, EGCG has shown cancer preventive activities [27,28]. Like melatonin, EGCG is also an antioxidant via its direct quenching of ROS or indirect induction of basal and/or Nrf2-dependent antioxidant defense systems [27,29]. On the other hand, at high doses and in certain environments, EGCG can act as a prooxidant owing to its auto-oxidation, resulting in the formation of the superoxide anion and hydrogen peroxide [30].…”
Section: Introductionmentioning
confidence: 99%
“…As the antioxidant and pro-oxidant activity of EGCG is not well established yet due to variation related to genetic background [99], doses, and pathological conditions [100], its use as a long-term treatment or supplement must be treated with caution.…”
Section: Discussionmentioning
confidence: 99%